Research in the history of economic thought and methodology. Vol. 39, part C : including a symposium on Frank Knight's Risk, uncertainty, and profit at 100 - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo; Emmett, Ross B. (Research in the history of economic thought and methodology, 2021)
Volume 39C of Research in the History of Economic Thought and Methodology, features a symposium marking the 100th anniversary of the publication of Frank H. Knight's Risk, Uncertainty, and Profit. The symposium features contributions from Per Bylund, Richard E. Wagner, our own Carlos Eduardo Suprinyak and his co-author, Thiago Oliveira, as well as an essay from guest editor Ross B. Emmett. The Volume also includes general-research essays from David C. Coker, J. Patrick Higgins, and Charles R. McCann, Jr.